Increased Expression of Multiple Co-Inhibitory Molecules on Malaria-Induced CD8+ T Cells Are Associated With Increased Function Instead of Exhaustion - Brandi, Johannes; Riehn, Mathias; Hadjilaou, Alexandros; Jacobs, Thomas (Frontiers in Immunology, 2022)
Activated cytotoxic CD8+ T cells can selectively kill target cells in an antigen-specific manner. However, their prolonged activation often has detrimental effects on tissue homeostasis and function. Indeed, overwhelming cytotoxic activity of CD8+ T cells can drive immunopathology, and therefore, the extent and duration of CD8+ T cell effector function needs to be tightly regulated. One way to regulate CD8+ T cell function is their suppression through engagement of co-inhibitory molecules to their cognate ligands (e.g., LAG-3, PD-1, TIM-3, TIGIT and CTLA-4). During chronic antigen exposure, the expression of co-inhibitory molecules is associated with a loss of T cell function, termed T cell exhaustion and blockade of co-inhibitory pathways often restores T cell function. We addressed the effect of co-inhibitory molecule expression on CD8+ T cell function during acute antigen exposure using experimental malaria. To this end, we infected OT-I mice with a transgenic P. berghei ANKA strain that expresses ovalbumin, which enables the characterization of antigen-specific CD8+ T cell responses. We then compared antigen-specific CD8+ T cell populations expressing different levels of the co-inhibitory molecules. High expression of LAG-3 correlated with high expression of PD-1, TIGIT, TIM-3 and CTLA 4. Contrary to what has been described during chronic antigen exposure, antigen-specific CD8+ T cells with the highest expression of LAG-3 appeared to be fully functional during acute malaria. We evaluated this by measuring IFN-γ, Granzyme B and Perforin production and confirmed the results by employing a newly developed T cell cytotoxicity assay. We found that LAG-3high CD8+ T cells are more cytotoxic than LAG-3int or activated but LAG-3low CD8+ T cells. In conclusion, our data imply that expression of co-inhibitory molecules in acute malaria is not necessarily associated with functional exhaustion but may be associated with an overwhelming T cell activation. Taken together, our findings shed new light on the induction of co-inhibitory molecules during acute T cell activation with ramifications for immunomodulatory therapies targeting these molecules in acute infectious diseases.